1970
DOI: 10.1073/pnas.65.4.939
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Genetic Organization in Higher Organisms, II. Complementation and Fine Structure of the Maroon-like Locus of Drosophila melanogaster

Abstract: Abstract. Mutants of the maroon-like complex, representative of the five known complementation classes, were subjected to fine structure mapping experiments utilizing a nutritional selective procedure which permits the survival of rare ma-l+ progeny from large-scale crosses. The analysis provides an internally consistent, unique map, colinear with the complementation map. Noncomplementers exhibit a polarized mapping distribution. In addition to ma-l+ recombinants, the selective medium permitted the survival of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1971
1971
1990
1990

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…In the latter case, a random strand analysis of recombination between maroon-like cistron mutants revealed that approximately half of the ma-l + exceptions exhibited exchange for the flanking markers. Utilizing the flanking marker recombinants, a unique internally consistent, linear, map of the ma-1 cistron was constructed which corresponds precisely with a complementation map (Finnerty, Duck & Chovnick, 1970). However, a half-tetrad analysis questioning the reciprocality of recombination events in heterozygotes for the most distant ma-1 alleles revealed that all of the events are non-reciprocal (Smith et al 1970a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, a random strand analysis of recombination between maroon-like cistron mutants revealed that approximately half of the ma-l + exceptions exhibited exchange for the flanking markers. Utilizing the flanking marker recombinants, a unique internally consistent, linear, map of the ma-1 cistron was constructed which corresponds precisely with a complementation map (Finnerty, Duck & Chovnick, 1970). However, a half-tetrad analysis questioning the reciprocality of recombination events in heterozygotes for the most distant ma-1 alleles revealed that all of the events are non-reciprocal (Smith et al 1970a).…”
Section: Discussionmentioning
confidence: 99%
“…In higher eukaryotes, such as Drosophila melanogaster, observations which may be inferred to reflect conversion events have been reported on more than several occasions (Baillie, Astell & Scholefield, 1966;Chovnick, 1958Chovnick, , 1961Chovnick, Lefkowitz & McQuinn, 1956;Finnerty, Duck& Chovnick, 1970;Green, 1960;Hexter, 1963;Welshons & von Halle, 1962). Rigorous confirmation of these events as conversions has awaited the development of appropriate genetic systems for systematic investigation.…”
Section: Introductionmentioning
confidence: 93%
“…The minimal molecular weight of a protein coded by the ma-l+ cistron [9] is about 15000. Intracistronic complementation [35] requires the product to be at least a dimer, meaning that the moiety in xanthine dehydrogenase coded by the ma-1 + locus should have a molecular weight of at least 30000.…”
Section: Hypothesesmentioning
confidence: 99%
“…Some of these alleles show intracistronic complementation, i.e., flies heterozygous for two different ma-1 alleles in trans position possess xanthine dehydrogenase activity [9].…”
mentioning
confidence: 99%
“…To date, mitotic conversion, or the recovery of non-reciprocal recombinant products, has been found in yeast and fungi (see Fogel & Mortimer, 1971). Non-reciprocal products of meiosis have been reported in three D. melanogaster loci: garnet (Chovnick, 1961;Hexter, 1963Hexter, , 1964, maroon-like (Finnerty, Duck & Chovniok, 1970) and rosy (Chovnick et al 1970;Ballantyne & Chovnick, 1971).…”
Section: (I) Double Reciprocal Recombinationmentioning
confidence: 96%